PENGARUH PELIMPAHAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN SEKTOR PEDESAAN DAN PERKOTAAN MENJADI PAJAK DAERAH TERHADAP REALISASI PENERIMAANNYA DI KOTA SURABAYA - Ramadhan, Jogi Fahrisal (Jurnal Akuntansi AKUNESA, 2014)
Tax Law and Regional Retribution Act No. 28 of 2009 regulated about handed tax property of rural an urban sectors. Local government have more responsibility for prepare well to adapted it before 2014. Purpose of this research is to determine the impact for Surabaya as a first time to applying this regulation after property tax no longer managed by central government, and how the regulation decrease acceptace of that sector. The approach used in this study is a qualitative approach. The result of this research are the reasons causes decreasing revenue than target after tax property of rural an urban sectors managed by Surabaya local goverments. Keywords: Regulation, Tax Property, Local Revenue.